Influence of the addition of montmorillonite in an epoxy powder coating applied on carbon steel - Piazza, Diego (2015)
Polymer coatings have been used for the corrosion protection of metal surfaces acting as a physical barrier against several corroding media. In spite of the good efficiency of these coatings their resistance is limited due to the presence of localized defects which give place to localized corrosion. Aiming to improve the barrier properties of these coatings this work has proposed the use of nanocomposites as powder coatings based on a standard formulation of a commercial powder varnish. Nanocomposites with 2 and 4 wt% contents of organophilic montmorillonite (OMMT) were obtained in the molten state through of a co-rotating twin-screw extruder. The application of the nanocomposite coatings was performed by electrostatic pulverization on mild steel panels. The coatings were characterized to determine their structure using X-ray diffraction (XRD). The morphologies of the coatings were assessed using transmission electron microscopy (TEM). Gloss and adhesion measurements and the flexibility and impact resistance of the coatings were included in the physical assessment of the coatings. The corrosion performance was evaluated by the salt spray test and by electrochemical impedance spectroscopy (EIS). The coatings with clays presented predominantly exfoliated structures, with good dispersion of OMMT in the epoxy matrix. The addition of OMMT reduced the impact resistance, flexibility and gloss but increased the barrier properties of the coatings. The best corrosion performance in NaCl solution was achieved for 4 wt% OMMT.